Sistem Informasi Penjualan dan Pembelian Oleh-oleh Khas Daerah Berbasis Web - Malau, Emerson P; Ndruru, Tri Historis Budi Mulia Xaverius (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
In a web-based sales and purchase information system for souvenirs typical of the area, the web has many functions which of course can assist sellers and buyers in making transactions. Sellers can provide and display whatever is in the store. Whether it's food, snacks, goods or anything else. Buyers can also order and request what items they want to buy, how much, and when they will be picked up. For each item, there will also be information about the item. What is it made of, price, and so on. Because it also displays information about all existing products, it is hoped that it will add to public knowledge about regional original products. This can also improve marketing and at the same time promote the area to the community so that they can get to know an area better. That's it. This information system will also facilitate buying and selling in the transaction process. where the buyer can choose to make a transaction via account transfer or directly (at the same time when picking up the goods). This information system will be made web-based. The web is used because the web is a medium that can be accessed from anywhere, anytime and anyone. And also through cell phones or personal computers. So that it can make it easier for anyone who wants to make a purchase transaction